Father of the bride. [videorecording (DVD)] Part II - Shyer, Charles; Martin, Steve, 1945-; Keaton, Diane; Williams-Paisley, Kimberly, 1971-; Short, Martin, 1950-; Hackett, Albert; Goodrich, Frances (Touchstone Home Entertainment : Distributed by Buena Vista Home Video, 1996)
While George Banks is trying to recapture his youth his daughter and wife announce they are pregnant.